A new Mediterranean species of Dolistenus (Diplopoda, Platydesmida, Andrognathidae), with an updated key for the genus and the first contribution for a barcode database of European Platydesmida - Recuero, Ernesto; Rodríguez-Flores, Paula C. (Zootaxa, 2020)
Dolistenus Fanzago, 1874 is a widespread Mediterranean millipede genus of the order Platydesmida, currently including three valid species, each with relict distributions. Here we describe a fourth species of Dolistenus, and characterize it using morphological and molecular (mitochondrial DNA) characters. We provide an updated key to the species of Dolistenus and the first COI barcode sequences for the new species and several other European representatives of the Andrognathidae (Platydesmida).